Standardisation of In Vitro Techniques for Rapid Multiplication of Holostemma Annulare K. Schum - Sophia A John (Department of Plantation Crops and Spices, College of Horticulture, 1996)
Studies were conducted on standardization of in vitro techniques for the rapid multiplication of Holostemma annulare K. Schum. At the Plant Tissue Culture Laboratory of the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara during 1993-1995. Surface sterilization was standardized for explants from different sources. For two to three month old explants from the glasshouse, treatment with 0.1 per cent mercuric chloride for 5 min or 10 min was found to be better. A combination of sterilants was necessary for mature explants taken either from the glasshouse or field. Explants collected in the months of January and February gave the lowest contamination rate. Early release of buds and further growth of nodal segments and shoot tip explants was better in MS media supplemented with BA. Cultures in medium containing KIN were short, robust, darker and with lesser number of buds and shoots than those in medium containing BA. Extremely low concentrations of TDZ could stimulate axillary bud proliferation. Additives like silver nitrate and activated charcoal could drastically reduce callus production in culture, but the shoot growth was also reduced with these additives. Nodal segments were better in respect of early release of buds, more number of longer shoots, nodes and buds than shoot tips. Higher temperature proved better than lower temperature for the growth of cultures. Also exposure to light was favourable for healthy growth of shoots. Proliferation rate was higher at higher concentrations of BA but the shoots were very swollen, weak and had to be subcultured as a clump into media containing lower concentrations of BA for healthy growth of shoots. Shoots could be proliferated at extremely low concentrations of TDZ. MS basal with full concentration of salts was better for better growth of shoots. When the best treatment in each subculture was given in sequence approximately 2 crores 37 lakh nodes could potentially be obtained over a period of 225 days. Maximum rooting, early rooting and more number of longer roots could be obtained in solid. MS basal media when shoots were kept for in vitro rooting. Ex vitro rooting of shoots was successful when they were treated with IBA 1000 mg1-1 as quick dip followed by planting in plastic pots filled with sand in the initial stages for early rooting and then transplanted to plastic or mud pots filled with cocofibe for vigorous growth of root and shoot portions. TDZ produced the highest callus index at relatively lower concentrations. The callus produced was hard, green in colour and compact. 2, 4-D proved better than NAA for obtaining more regenerative callus among the auxins tried. Leaf segments (with or without petiole attached) oriented with the abaxial surface touching the solid medium supplemented with 2,4-D and exposed to light alone produced embryoids after one or two subcultures into MS medium with lower concentrations of 2,4-D. The embryoid production could be triggered if the calli were subcultured to liquid MS basal medium and when further transferred to solid media alone produced elongation of such embryoids. But the original explants had to be raised in MS medium supplemented with either TDZ or KIN as cytokinin for the embryoids to form subsequently. Encapsulated beads were successfully formed with nodal segments using 2.5 per cent sodium alginate and 75 mM calcium chloride with a complexation time of 30 min and the beads could be stored successfully for 15 days at room temperature and upto 40 days at 40 C. The peroxidase isozyme pattern of the leaves and roots from in vitro plantlets and in vivo plantlets were similar having the same number of bands.